The effects of corporate reputation and compensation disclosure on investor judgments - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2019)
Regulators have increased the disclosure requirements of top executives as part of corporate governance reform. This study examines how trust arising from a firm’s corporate reputation will interact with top executive compensation disclosure to influence investor judgments. This study used a 2 X 2 between subjects experimental design, with corporate reputation (good versus bad) and pay ratio (high versus low) as independent variables to test the hypotheses. The key findings show that if the firm with a good corporate reputation discloses a high pay ratio, participants punished the good reputation firm more than the bad reputation firm, demonstrating a negative violation of expectations. On the other hand, if the firm with a bad corporate reputation discloses a low pay ratio, participants rewarded the bad reputation firm more than the good reputation firm, demonstrating a positive violation of expectations. The results of this study may be limited by its particular circumstances of corporate reputation and compensation disclosure, making generalizations of the findings to other settings difficult.